Reviews of Environmental Contamination and Toxicology - Whitacre, David M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
CONTENTS FOREWORD PREFACE Parameters for Pyrethroid Insecticide QSAR and PBPK/PD Models for Human Risk Assessment James B. Knaak, Curtis C. Dary, Xiaofei Zhang, Robert W. Gerlach, R. Tornero-Velez, Daniel T. Chang, Rocky Goldsmith and Jerry N. Blancato Index
Foreword -- Preface -- Parameters for Pyrethroid Insecticide QSAR and PBPK/PD Models for Human Risk Assessment -- Index.
Keywords: Environmental sciences; Environmental management; Environmental toxicology; Waste disposal; Environment; Ecotoxicology; Environmental Management; Waste Management/Waste Technology